Patriotism and the Image of Iraq and Its Symbols in the Poetry of Yahya al-Samawi - Shahrokh, Mehdi; Sadat Eshkevar, Soleiman; Babaei damtasoj, Ali (Al-Adab Journal, 2020)
Every literary scholar usually draws the elements of thought and emotion, either joyful or sad, from their homeland. The resistance poet, Yahya Al-Samawi, was born and raised in Iraq and so felt the troubled political and security conditions of his country firsthand. Therefore, his poetry is purely patriotic, which encouraged his fellow countrymen to revolt against the regime of Saddam Hussain before its fall in 2003 and against the foreign occupiers after that. This paper relies on the descriptive-analytical methodology to investigate patriotism, the image of Iraq and its implications in the poetry of Al-Samawi. The results of the study show that Iraq as his homeland is the first reason for the poet to write protest and political poetry. This has given his nationalist poetry genuine sentiments, where the poet calls out from the bottom of his heart to portray his homeland Iraq and to reflect his people’s woes, sorrows and afflictions. As a result, his poetry is replete with Iraqi symbols, by virtue of which, he attempts to uncover the political conspiracies by the tyrannical regime and foreign colonizers. Symbols such as the palm tree, famous cities of Iraq such as Baghdad, the Tigris and the Euphrates, and great historical characters and legacies such as Imam Hussain (AS) the symbol of revolution against tyrannies, are very frequent in his poetry. Despite the dichotomy found in his poetry due to his patriotic sentiments and his longing for the homeland on the one hand, and his life in exile on the other hand, his genuine affection for his homeland has not been negatively affected.